Quelques nouvelles espèces de Myxosporidies, du genre Ceratomyxa Thélohan, 1895 parasites des poissons marins du Sénégal, Afrique de l'Ouest - Kpatcha, T.; Diebakate, C.; Faye, N.; Toguebaye, B. (Parasite, 1996)
Seven species of Ceratomyxa were found in the gall-bladder of marine fishes collected from the coats of Senegal. These species were: C. acanthuri n. sp. from Acanthurus monroviae, C. fistulariae n. sp. from Fistularia petimba, C. lagocephali n. sp. from Lagocephalus laevigatus, C. syacii n. sp. from Syacium micrurum, C. trachinocephali n. sp. from Trachinocephalus myops., C. trichiuri n. sp. from Trichiurus lepturus and C. truncata Thélohan, 1895 from Sardinella maderensis and Sardinella aurita.